Climate Change and Forest Governance: Lessons from Indonesia - Latif, Birkah (Indonesia Law Review, 2015)
Climate change and forest governance have always been discussed between scholars, governments and all stakeholders who engage in the issues. Discussions have been arisen from time to time on how devastating the impacts of environment loss caused by the acts of people. These impacts have brought people and countries to see the problems more seriously and attentively.